The Effectiveness of Using the Mingle Model as a Teaching Strategy to Improve Students' Speaking Skills - Sari Fatmawati Jalisah; Indah Tri Purwanti; Novitri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to determine the effectiveness of the Mingle Model in improving the speaking skills of 10th grade students at State Vocational High School. This study was motivated by students' low self-confidence, limited vocabulary, and lack of fluency in speaking English. This study used a quantitative approach with a one-group pre-test–post-test pre-experimental design. The research sample was determined using the cluster random sampling technique, and the selected class was class X Samsung - Software and Game Development 2, consisting of 37 students. The Mingle Model was implemented in six sessions. Data were collected using a monologue recount text speaking test before and after the treatment, which were assessed based on the aspects of grammar, vocabulary, pronunciation, and fluency. The results showed that the average pre-test score of 46 increased to 81 on the post-test. The paired sample t-test showed a significant difference between the pre-test and post-test results (t = -42.409, Sig. = 0.000). In addition, the N-Gain analysis result of 0.66 showed that the Mingle Model was fairly effective. Based on these results, it can be concluded that the Mingle Model is effective in improving students' speaking skills through communicative and interactive learning.